2018
DOI: 10.1038/s41416-018-0273-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of second cancers at sites associated with HPV after a prior HPV-associated malignancy, a systematic review and meta-analysis

Abstract: Background High-risk human papilloma viruses (HPV) are a causative agent of anogenital and oropharyngeal cancers. Patients treated for a preinvasive or invasive HPV-associated cancer may be at increased risk of a second such malignancy. Methods We performed a systematic review and random effects meta-analysis to estimate the risk of HPV-associated cancer after prior diagnosis. Studies reporting second cancers at anogenital and oropharyngeal sites after prior diagnoses (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
1
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 79 publications
3
63
1
4
Order By: Relevance
“…Elevated SIR for anal cancer following cervical or vulvo-vaginal cancer are well established. 10 However, the current work highlights some substantial differences between these gynecological cancers.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Elevated SIR for anal cancer following cervical or vulvo-vaginal cancer are well established. 10 However, the current work highlights some substantial differences between these gynecological cancers.…”
Section: Discussionmentioning
confidence: 76%
“…Thus, there exist a number of groups at known elevated anal cancer risk. These include men who have sex with men (MSM), 8 persons living with HIV (PLHIV), 9 women with HPV‐related gynecological cancer or precancerous lesions, 10 as well as iatrogenically immunosuppressed recipients, most notably solid organ transplant recipients (SOTRs) 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to understand whether HPV infections in 1 anatomic site can be associated with infection at other sites. Other studies [6][7][8] have shown these links between cervical and anal infections and disease, and now the study by Schlecht et al 1 associates cervical HPV detection with oral HPV detection, although not yet with disease.…”
Section: Schlecht Et Al 1 Did An Excellent Job Collecting Sexual Histmentioning
confidence: 92%
“…The systematic review and meta-analysis study "Increased risk of second cancers at sites associated with HPV after a prior HPVassociated malignancy, a systematic review and meta-analysis", presented by Gilbert et al and published in BJC, has been read by us with interest. 1 Our meta-analysis research team would like to bring into attention a few valid improvements to the paper. Therefore, this study may serve a better position as a citable article.…”
mentioning
confidence: 99%